About Development of the Typology of Preschool Education Programs - Doronova T.N.; Doronov S.G.; Кhaylova E.G. (Психолого-педагогические исследования, 2020)
All-round development of a child in kindergarten is possible only when using educational programs that perform the function of structuring the entire volume of developmental influences on a child in kindergarten. Currently, this requirement is not fully observed, which leads to the loss or, on the contrary, unproductive duplication of part of the content of preschool education. This state of affairs necessitates the development of a typology of programs. Also, the typology of the program is the basis for building objective links between the goals of educational activities and its actual results. But, at present, connections of this kind can be built only through individual psychodiagnostic examinations, which is unacceptable for real pedagogical practice for a number of reasons. In this article, the authors, relying on the psychological and pedagogical concept of N.A. Korotkova, designing the structure of the educational program, which considering the whole variety of possible events occurring in the preschool educational organization and allowing, without using additional semantic links, to determine the course of children's development based on the manifestation of various types of initiative in their activities.